A discrete-continuum coupled numerical method for fracturing behavior in concrete dams considering material heterogeneity. (25th October 2021) - Qin, Xiangnan; Guo, Jinjun; Gu, Chongshi; Chen, Xudong; Xu, Bo
Highlights: A systematic computational approach is proposed for fracturing behavior in concrete dams considering material heterogeneity. Batch insertion of cohesive element and parameter randomization of material property are novelly realized. Hydraulic and thermal loads are numerically investigated in discrete-continuum mesh scheme. The feasibility of the numerical model is verified with application in a practical concrete dam. Abstract: This study aims to propose a systematic discrete-continuum coupled computational approach for fracturing behavior in concrete dams, with consideration of material heterogeneity. Innovative techniques are developed to realize batch insertion of cohesive element and parameter randomization of material property, and their feasibility and efficiency are verified with fracturing modelling of concrete specimens. Based on numerical investigation of hydraulic and thermal loads in discrete-continuum mesh scheme, a complete approach of fracturing modelling in concrete dams with stochastic material property is established. A case study with Chencun arch dam is conducted, and the numerical results exhibit high consistency with observational information, which demonstrates that the proposed method is feasible to characterize the mechanical performance and fracturing behavior of concrete dams with material heterogeneity.